THE ROLE OF PROFITABILITY AS A MEDIATOR BETWEEN COMPANY VALUE, COMPANY LIQUIDITY, AND DIVIDEND POLICY IN COMPANIES IN THE 2017-2021 PERIOD - Bakar, Abu; Delila Rambe (Program Studi Akuntansi Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2025)
The purpose of this study is to determine the effect of firm size, firm value, and liquidity on dividend policy and to what extent profitability, as an intervening variable, mediates the relationship between firm size, firm value, and liquidity on dividend policy in coal companies listed on the Indonesia Stock Exchange. The population used in this study was coal companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample selection technique used was purposive sampling. Path analysis was used for analysis. The results showed that firm value and liquidity significantly influence profitability, while firm size does not. Firm size, firm value, and liquidity do not significantly influence dividend policy. Profitability does not mediate the effect of firm size, firm value, and liquidity on dividend policy.